By Regulating the NLRP3 Inflammasome Can Reduce the Release of Inflammatory Factors in the Co-Culture Model of Tuberculosis H37Ra Strain and Rat Microglia - Xie, Zhen; Hui, Hao; Yao, Qian; Duan, Yan; Li, Wu; Cheng, Ye; Zhang, Meng; Tian, Ye; Zhao, Gang (Frontiers in Cellular and Infection Microbiology, 2021)
Abstract Objective: Tuberculosis infection of the Central Nervous System can cause severe inflammation in microglia, and NLRP3 inflammasome is also an important source of inflammation in microglia. Therefore, in this study, we used a co-culture model of rat microglia and tuberculosis H37Ra strain to explore the influence of tuberculosis infection on the NLRP3 inflammasome in microglia and its regulation mechanism. Methods: Culture primary microglia from SD rats and co-culture with tuberculosis H37Ra strain for 4 hours to establish a co-culture model. At the same time, MCC950, Z-YVAD-FMK, BAY-11-7082, Dexamethasone, RU486, BzATP, BBG and extracellular high potassium environment were used to intervene in the co-cultivation process. Subsequently, western blot, real-time fluorescent quantitative PCR, ELISA and other methods were used to detect the changes of NLRP3 inflammasome-related molecules in microglia. Results: After co-cultivation, the NLRP3 inflammasomes in microglia were activated and released a large amount of IL-18 and IL-1. By regulating NLRP3 inflammasome complex, caspase-1, NF-B and P2X7R during the co-culture process, it can effectively reduce the release of IL-18 and IL-1, and reduce the mortality of microglia. Conclusion: Our results indicate that the NLRP3 inflammasome pathway is an important part of the inflammatory response of microglia caused by tuberculosis infection. Through the intervention of NLRP3 inflammasome pathway, it can significantly reduce the inflammatory response and mortality of microglia during the tuberculosis H37Ra strain infection. This study can help us further understand the mechanism of inflammatory response in central nervous system tuberculosis infection and improve its treatment.